ETNOMATEMATIKA KAIN ADAT SUKU SAMAWA DI PROVINSI NUSA TENGGARA BARAT - Fitasari, Baiq Diah; Slamet Mardiyanto Rahayu (Yayasan Nusantara Hasana Berdikari, 2025)
Indonesia is a country consisting of many ethnic groups. One of them is the Samawa tribe in West Nusa Tenggara. Each tribe has a culture and cultural products, such as traditional cloth. Culture in each region contains historical values, social communities, beliefs, and knowledge, including mathematics. Culture and cultural products such as traditional cloth can be used to teach mathematics. Ethnomathematics is a branch of mathematics that connects culture with mathematics. Until now, there has been no research that examines the ethnomathematics of traditional cloth of the Samawa tribe. Therefore, it is necessary to conduct this research which aims to analyze the ethnomathematics of traditional cloth of the Samawa tribe. Data collection was carried out through interviews, observations, and documentation. Data is displayed in the form of tables and images. Furthermore, it is analyzed descriptively. Overall, the traditional cloth of the Samawa Tribe is not only traditional clothing but also a medium for expressing local values ​​and knowledge, including mathematical concepts. The ethnomathematics in it combines art with mathematical logic in everyday culture, which ultimately becomes part of the identity of the Samawa Tribe.